Limiting factors of using consistencies for feeding patients with dysphagia: perception of the main caregiver - Vargas García, Miguel Antonio; Delprado Aguirre, Andrés Fernando; Posada Salazar, Valeria; Grajales Gómez, Laura Daniela (Revista de Investigación en Logopedia, 2023)
Since dysphagia is of long duration, the actions of approaching the patient with this condition require the direct and permanent participation of the main caregiver. People with this role define the processes involved in the care of intake at home. From this perspective, the caregiver of the subject with dysphagia would be the one who should be fully trained in the aforementioned processes, not only as knowledge of the techniques used in rehabilitation but also as a form of approval of their use. In order to describe the relationship of the main caregiver in the use and management of consistency modification, a mixed registration process is proposed that allows the caregiver’s perception of the use of this technique to be evidenced. The work is interesting as it shows how limiting aspects are concatenated with social determinants of health. So that, considering the economic perspective, responsibility, and knowledge of the management of consistencies, this work places dysphagia as complicated issue for the caregiver to deal with, due to the different realities.